PENERAPAN ACTIVITY BASED COSTING DALAM PENENTUAN TARIF JASA RAWAT INAP DI RUMAH SAKIT UMUM DAERAH HJ. ANNA LASMANAH KABUPATEN BANJARNEGARA - Ghonimah Zumroatun Ainiyah; Siti Maesaroh (STIE Pelita Nusantara Semarang, 2020)
The phenomenon of the Hj. Anna Lasmanah Banjarnegara is less able to provide proper and accurate information for management, which can affect the profitability of the hospital. The objectives of this study: 1) describe the cost calculations used to determine inpatient service rates in 2019, 2) analysis cost calculations using an activity based costing system in determining the rates for inpatient services at Hj. Anna Lasmanah HospitalThe focus of this research is to calculate the cost of inpatient care and analysis the possibility of implementing an activity-based costing system as an alternative in determining the cost of hospitalization. The data analysis used in this research is quantitative descriptive analysis. Namely by comparing the results of the calculation of inpatient rates for patients with an activity based costing system with inpatient rates determined by the hospital.There are differences in the results of the calculation of inpatient rates for each class between the traditional method and the activity based costing system. This difference results in lower or higher tariffs. The results of the calculation show that the inpatient service tariff using an activity based costing system for VVIP A class is IDR 437,658, VVIP B class IDR 395,674, Class I IDR 378,180, Class II IDR 320,249, Class III IDR 319,374. It can be seen from these results that when compared with conventional methods, the activity based costing system provides higher hospitalization rates for Class I, II and III. The rates are set lower for Class VVIP A and VVIP B. Activity based costing system can provide more precise accuracy because it has made calculations according to the resources consumed by each class